Dampak Game Edukatif pada Perkembangan Kognitif Anak Usia Dini - Istnain Alfajri Husain (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The development of technology in the world of education has brought significant changes in learning methods, including in Early Childhood Education (PAUD). One of the innovations that is increasingly developing is the use of educational games as a learning medium. Educational games are designed to stimulate children's cognitive abilities through various challenges involving problem solving, logical thinking, and creativity. This literature study aims to examine the impact of educational games on the cognitive development of early childhood by analyzing various recent studies. The results of the study show that educational games can improve memory, concentration, and critical thinking skills in children. However, excessive and unsupervised use also has the potential to have negative impacts, such as digital dependence and lack of social interaction. Therefore, it is important for educators and parents to integrate educational games in a balanced manner with other learning methods. This study is expected to be a reference for educators and researchers in developing effective technology-based learning strategies for early childhood.